2005
DOI: 10.1002/ange.200500408
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Axially Chiral Amino Acid with a Binaphthyl Backbone as an Organocatalyst for a Direct Asymmetric Aldol Reaction

Abstract: The direct catalytic asymmetric aldol reaction is one of the most fundamental transformations in organic synthesis, and several efficient asymmetric methodologies for this reaction using chiral metal catalysts [1] and organocatalysts [2][3][4] have recently been developed, of which catalysis by proline [2, 3] and its derivatives [4] have been extensively explored. However, the reactivity and selectivity of some of these prolinecatalyzed aldol reactions have serious limitations because of the difficulty in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 33 publications
0
11
0
3
Order By: Relevance
“…There are a number of research works on the proline-type organocatalysts, for example: Jørgensen et al reported the organocatalytic diastereo-and enantioselective annulation reactions in the construction of optically active 1,2-dihydroisoquinoline and 1,2-dihydrophthalazine derivatives [111]; Maruoka et al reported the design of an axially chiral amino acid with a binaphthyl backbone as an organocatalyst (Structure A) for a direct asymmetric aldol reaction [112]; Jørgensen et al reported organocatalytic conjugate addition of malonates to α,β-unsaturated aldehydes and finished the asymmetric formal synthesis of (−)-paraxetine [113]; Zhao et al reported organocatalytic enantioselective synthesis of α-hydroxy phosphonates via a proline-catalyzed asymmetric cross aldol reaction of activated ketones [114]; proline derivatives were reported to be involved into the organocatalytic direct Michael reaction of ketones and aldehydes with nitroalkenes [115,116]; Barbas, III explored 3-pyrrolidinecarboxylic acid (Structure B) for direct catalytic asymmetric Mannich-type reaction of unmodified ketone with anti-selectivity [117]; Palomo reported highly efficient asymmetric Michael addition of aldehyde to nitroalkene catalyzed by trans-4-hydroxyprolylamide (Structure C), with 4-hydroxy group involved in the reaction transition state [118]; Wang and Wang [119] reported the directly, highly enantioselective Michael addition of aldehyde to nitro styrene catalyzed with pyrrolidine sulfonamide (Structure D).…”
Section: Proline-catalyzed Asymmetric Reactionmentioning
confidence: 99%
“…There are a number of research works on the proline-type organocatalysts, for example: Jørgensen et al reported the organocatalytic diastereo-and enantioselective annulation reactions in the construction of optically active 1,2-dihydroisoquinoline and 1,2-dihydrophthalazine derivatives [111]; Maruoka et al reported the design of an axially chiral amino acid with a binaphthyl backbone as an organocatalyst (Structure A) for a direct asymmetric aldol reaction [112]; Jørgensen et al reported organocatalytic conjugate addition of malonates to α,β-unsaturated aldehydes and finished the asymmetric formal synthesis of (−)-paraxetine [113]; Zhao et al reported organocatalytic enantioselective synthesis of α-hydroxy phosphonates via a proline-catalyzed asymmetric cross aldol reaction of activated ketones [114]; proline derivatives were reported to be involved into the organocatalytic direct Michael reaction of ketones and aldehydes with nitroalkenes [115,116]; Barbas, III explored 3-pyrrolidinecarboxylic acid (Structure B) for direct catalytic asymmetric Mannich-type reaction of unmodified ketone with anti-selectivity [117]; Palomo reported highly efficient asymmetric Michael addition of aldehyde to nitroalkene catalyzed by trans-4-hydroxyprolylamide (Structure C), with 4-hydroxy group involved in the reaction transition state [118]; Wang and Wang [119] reported the directly, highly enantioselective Michael addition of aldehyde to nitro styrene catalyzed with pyrrolidine sulfonamide (Structure D).…”
Section: Proline-catalyzed Asymmetric Reactionmentioning
confidence: 99%
“…The authors used the axially chiral organocatalyst 13, a derivative of the catalyst they had previously employed in the direct asymmetric aldol reaction between acetone and aldehydes. [41] The key feature of 13 was the large distance between the amino and the acid groups. This separation favored the preferential formation of the syn-enamine intermediate B, thus affording the anti-Mannich product via transition state TS-II (Scheme 17).…”
Section: Development Of New Catalystsmentioning
confidence: 99%
“…Maruoka und Mitarbeiter nutzten ihre Erfahrungen mit der axialen Chiralität [6a] und aus Arbeiten über axial-chirale nichtnatürliche Aminosäuren in der Enaminkatalyse. [104] Das außergewöhnliche chirale Aminosulfonamid XXI katalysierte die anti-selektive Mannich-Reaktion für sämtliche getestete Substrate mit einem Diastereomerenverhältnis von mindestens 11:1 und 97 % ee (Abbildung 5 c). [102] Dabei verbleibt als einziger Übergangszustand, der vollständig von der doppelten Aktivierung des Aldehyds (durch das Amin im siebengliedrigen Ring) und des Elektrophils (durch das saure Proton des Sulfonamids) profitiert, der zehngliedrige cyclische Übergangszustand H, bei dem die Si-Seite des Imins sich an die Re-Seite des E-Enamins anlagert.…”
Section: Aufsätzeunclassified